Fifth Annual IEEE International Conference on Pervasive Computing and Communications Workshops (PerComW'07) 2007
DOI: 10.1109/percomw.2007.98
|View full text |Cite
|
Sign up to set email alerts
|

Public-Key Cryptography for RFID-Tags

Abstract: RFID-tags are a new generation of bar-codes with added functionality. An emerging application is the use of RFIDtags for anti-counterfeiting by embedding them into a product. Public-key cryptography (PKC) offers an attractive solution to the counterfeiting problem but whether a publickey cryptosystem can be implemented on an RFID tag or not remains unclear. In this paper, we investigate which PKCbased identification protocols are useful for these anticounterfeiting applications. We also discuss the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(61 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…The zero-knowledge property may be useful in an uncontrolled in-the-field code update, debug or test environment where the communication channel between the test server and JTAG is untrusted and the secret need not be shared or linked to a communicating entity. Moreover, Schnorr is a very established protocol, and is used in Radio Frequency Identification (RFID) protocols [16,17]. The related ECC-based Schnorr authentication protocol [13] is described in appendix A.…”
Section: Secure Test Authentication Based On Schnorr Protocolmentioning
confidence: 99%
“…The zero-knowledge property may be useful in an uncontrolled in-the-field code update, debug or test environment where the communication channel between the test server and JTAG is untrusted and the secret need not be shared or linked to a communicating entity. Moreover, Schnorr is a very established protocol, and is used in Radio Frequency Identification (RFID) protocols [16,17]. The related ECC-based Schnorr authentication protocol [13] is described in appendix A.…”
Section: Secure Test Authentication Based On Schnorr Protocolmentioning
confidence: 99%
“…There are some papers which propose to use PKC-based RFID systems [25], [22], [2], [11]. In [25] no specific authentication protocol is mentioned, and the Schnorr protocol [18] and the Okamoto protocol [16] are adopted in [22] and [2] respectively.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In [25] no specific authentication protocol is mentioned, and the Schnorr protocol [18] and the Okamoto protocol [16] are adopted in [22] and [2] respectively. However, it is shown that these two protocols are not proper for RFID systems due to their vulnerability against the tracking attack [11].…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementations must have a small footprint not to exceed the costs, and they have to be designed for low power in order to allow a certain reading range. A lot of proposals have been published so far that deal with lightweight cryptography for RFID by using coupon-based signature functions like GPS [23,18], stream ciphers [7,12,9], asymmetric algorithms like ECC [30,4], or symmetric algorithms like AES [10], PRESENT [6], SEA [28], HIGHT [13], or DES variants [22]. At the time, the security features of conventional RFID tags range from simple secure memory-lock functionalities to integrated cryptographic engines like Mifare [19], SecureRF [26], or CryptoRF [2].…”
Section: Introductionmentioning
confidence: 99%